Interpretive Structural Modelling: Faktor-faktor Kunci Penyediaan Beras di Kabupaten Penajam Paser Utara - Adi, Aswan; Rachmina, Dwi; Krisnamurthi, Y Bayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The study of key factors is aimed at finding out what factors have the most influence on the availability of rice, which can be used as a consideration for policy formulation to increase the availability of rice in Penajam Paser Utara (PPU). The relocation of the new Nusantara Capital City (IKN) has caused a significant increase in the number of people and affected the balance of rice availability in PPU. The analysis method used is Interpretive Structural Modelling (ISM) analysis by looking at the driver power (DP) and the level of dependence (D) on each variable (factor). The results of the analysis have 14 sub elements (factors) spread into independent, linkage, and dependent positions, where each position will describe the role and influence given to the availability of rice in PPU. In conclusion, the key factors in the rice supply sector (average DP=0.89 and D=0.43) include land expansion, farmer institutions, counseling, and conversion emphasis. Policy implications include land expansion through paddy field printing programs in potential areas, institutional strengthening to reduce land conversion, and effectiveness of extension activities.